Visual support of optimal decisions in spatial networks - Dodonov, A. G.; Dodonov, V. A.; Kuzmichov, A. I. (Інститут проблем реєстрації інформації НАН України, 2017)
The investigation deals with complex application of graph visualization and business analytics for obtaining solutions of better quality, which is difficult to do utilizing traditional means, so graphs have played a role in many of those solutions. The function of a graph is to represent links between things such as a spatial network, revealing the organization structure. Relationships are fundamental for the spatial network, which is one of the reasons of graph analysis and visualization having so much potential for value. Nowadays, several of our most significant research and software development efforts are, in essence, graph-based. The graph-based approaches gain deeper understanding of the dynamics of organizational and business processes.The practice of optimization simulation of communication problems in spatial networks is faced with the need to quickly obtain the corresponding image with the optimal plan. The use of computer-rendered visualization for decision-making in business is a relatively recent phenomenon. Thus, the composition of available graph visualization software used by ordinary PCs is offered. Its usage allows obtaining weighted management decisions for dynamically changing values of data sets using the constructed graph on the results of optimization solutions.